Community-Acquired Antibiotic Resistance in Urinary Isolates from Adult Women in Canada - Warren J McIsaac; Tony Mazzulli; Joanne Permaul; Rahim Moineddin; Donald E Low (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: There are currently limited data regarding the prevalence of antimicrobial-resistant organisms causing community-acquired urinary tract infections among adult women in Canada. Trimethoprim-sulfamethoxazole (TMP-SMX) is the recommended first-line empirical antibiotic treatment, unless resistance of Escherichia coli to TMP-SMX exceeds 20%.